THE EFFECT OF SERVICE QUALITY, PHYSICAL ENVIRONMENT, PRODUCT DIVERSIFICATION, AND PRICE PERCEPTION ON CUSTOMER LOYALTY OF TOKO TANI JAYA IN BANYUWANGI REGENCY - Faizah, Kurnia; Naely, Muhammad; Winahyu, Pawestri (Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine and analyze the influence of service quality, physical environment, product diversification and price perceptions on customer loyalty at the Tani Jaya Store in Glenmoren District. The location of this research is at the Tani Jaya Shop in Kalibaru District, Banyuwangi Regency. This type of research uses quantitative methods with a sample size of 150 respondents and uses representative sampling techniques using data collection techniques in the form of questionnaires to respondents. The data analysis technique for this research uses instrument testing, classical assumptions and multiple linear regression. The analysis results obtained show that service quality, physical environment, product diversification and price perception have a positive and significant effect, both partially and simultaneously, on customer loyalty at Tani Jaya Stores, with a level of influence contribution of 0.769 or 76%.